Intravitreal Bevacizumab for Macular Edema Secondary to Retinal Vein Occlusion - Parajuli, Anil; Joshi, Purushottam; Subedi, Prabha; Pradhan, Chandni (Nepalese Journal of Ophthalmology, 2020)
Introduction: The most common cause of vision loss in cases of Retinal vein occlusion (RVO) is due to macular edema. This study was conducted to examine the effect of intravitreal bevacizumab (IVB) in the treatment of macular edema secondary to RVO. Materials and methods: The authors conducted a retrospective study of 94 eyes (N) of 92 patients with macular edema associated with decreased visual acuity secondary to RVO who were treated with IVB. Patients received IVB at baseline, 1 month and 2 months. At each follow up patients were evaluated and re-injected if necessary. Results: The mean age of the patients was 56.6 ±11.51 years. The average number of injections per eye was 2.1 ± 0.87. The baseline median central macular thickness (CMT) and best-corrected visual acuity (BCVA) in LogMAR was 465.00μm (Min 254μm, Max 1218μm) and 1.00 (Min 0.30, Max 2.28), respectively. The median CMT at one month following first, second and third dose of IVB was 258μm (N=94, Z= -7.64, p <0.001), 261μm (N=63, Z= -0.17, p=0.86), and 292μm (N=41, Z= -0.21, p= 0.83), respectively. The median LogMAR BCVA at one month following first, second and third dose of IVB was 0.60 (N=94, Z= -5.70, p < 0.001), 0.60 (N=63, Z= -1.69, p=0.09), and 0.60 (N=41, Z= -0.03, p=0.97), respectively. Pre-operative BCVA was the best predictor of the final visual outcome after IVB in cases of RVO. None of the patients developed any serious ocular or systemic complications due to IVB. Conclusion: IVB is an effective and safe treatment for macular edema associated with decreased visual acuity secondary to RVO. The most beneficial effect of IVB is seen at one month after the first dose. The efficacy of subsequent doses could not be established in this study